Genetic evidence for the association between per- and polyfluoroalkyl substances exposure and rheumatoid arthritis risk - Hang Xu; Jiachen Liu; Xiaorui Qiu; Jiawei He; Weichu Sun (Medicine, 2026)
Per- and polyfluoroalkyl substances (PFAS), particularly perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS), are persistent environmental pollutants with potential immunotoxic effects. Emerging epidemiological evidence suggests a link between PFAS exposure and autoimmune diseases, including rheumatoid arthritis (RA). However, the causal nature of this relationship remains unclear. Genetic instruments for circulating PFOA and PFOS levels were obtained from genome-wide association studies of European populations, while RA outcome data were sourced from the FinnGen consortium and United Kingdom Biobank. Associations were evaluated using multiple Mendelian randomization (MR) methods to assess the robustness of the findings. The inverse variance weighted method served as the primary approach. Additional methods, including MR-Egger, weighted median, simple mode, weighted mode, maximum likelihood estimation, and robust adjusted profile score, were applied to address potential pleiotropy and weak instrument bias. Sensitivity analyses, including Cochran Q -test for heterogeneity, MR-pleiotropy residual sum and outlier (MR-PRESSO) for pleiotropy detection, and leave-one-out analysis, were performed to validate the robustness of the findings. MR analysis identified a significant association between genetically predicted PFOA levels and increased RA risk (odds ratio = 1.87, 95% confidence interval [1.13–3.11], P = .015). Similarly, genetically predicted PFOS levels were positively associated with seropositive RA risk (odds ratio = 1.14, 95% confidence interval [1.00–1.29], P = .049). Sensitivity analyses confirmed the robustness of these findings, and reverse MR analysis did not indicate bidirectional causality. Our findings provide genetic evidence suggesting a potential association between PFAS exposure and RA risk. Given the widespread environmental persistence of PFAS, further investigation into potential health impacts and strategies to reduce exposure may be warranted. Further mechanistic studies are warranted to elucidate the biological pathways underlying the potential relationship between PFAS exposure and RA.